The economic value of grassland products - Nábrádi , András (Applied Studies in Agribusiness and Commerce, 2007)
The economic value of grassland products is not always clear. In addition to demonstrating the social benefits of grassland products, the objective of the present study is to present the value of their diverse forms of utilization and their definitions in practice. This study groups marketable and non-marketable grass products and introduces a new category, the animal husbandry value of grasses. Among other factors, economists differ from researchers in other areas of science, as they are basically motivated by three issues The first question economists always raise is: “What can it be used for?”, the second is: “What is it worth?”, and the third is: “How can it (its value) be determined?” Any answers to any further questions are subordinated to the answers to these three.